Draft Sixth Five Year Plan 1978-1983 Under Land Reforms and Surveys - Planning Commission (Planning Commission, 1977)
The most crucial problem, however, is the existing -practice of hum cultivation with all its discard existing -practice of hum cultivation with all its discard cultivation, the agricultural lands allotted under Permit system in the past are being brought under Periodic Patta system for the purpose of eventual conversion into regular settlement under the Mizo District (Agricultural Land) Act, 1903 and the Rules made there under Such regular settlement by issue of Land Settlement Certificates in respect of Agricultural lands will enable the cultivator to enjoy the status of Land holders with all the accompanying benefits like inheritance and transfer. There being huge cases of such allotments under Permits to be converted into Periodic Patta and eventual settlement by issue of Land Settlement Certificates, the existing staff alone is unable to cope with the case effectively
Directorate of Land revenue Settlement Mizoram: Aizawl
Directorate of Land revenue Settlement Mizoram: Aizawl
Keywords: Cadastral Survey; Topographical Survey; Machinery and Equipment; Soil Conservation department; Organization and Infrastructure; Cash Crop and Horticulture Plantation; Village Grouping Centre Development; Miscellaneous Soil Conservation Scheme; Management of Village Grazing Ground; Agricultural and Rural Development; Veterinary Services and Animal Health; Milk Pocket on Private Sector